2014
DOI: 10.1002/2014gl060464
|View full text |Cite
|
Sign up to set email alerts
|

Martian meteorites and Martian magnetic anomalies: A new perspective from NWA 7034

Abstract: We present the magnetic properties of the Noachian Martian breccia NWA 7034. Among the 25 unpaired Martian meteorites studied to date, NWA 7034 has a unique magnetic mineralogy. It contains about 15 wt % of iron oxides as magnetite that has experienced cation substitution and partial alteration to maghemite, with about a quarter of the oxides being pure maghemite. It also contains oxyhydroxides in the form of superparamagnetic goethite. The presence of maghemite and goethite makes NWA 7034 the most oxidized Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 32 publications
(45 reference statements)
6
65
0
Order By: Relevance
“…; Gattacceca et al. ). Magnetic anomalies are restricted spatially but the 3 μm absorption indicating dust rich in Fe 3+ is widespread on Mars.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Gattacceca et al. ). Magnetic anomalies are restricted spatially but the 3 μm absorption indicating dust rich in Fe 3+ is widespread on Mars.…”
Section: Discussionmentioning
confidence: 98%
“…Abundant fine‐grained magnetite and maghemite explain the breccia's magnetic properties especially the high saturation remanence (Gattacceca et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Gattacceca et al. ). The acquisition of a chemical remanent magnetization (CRM) or a thermo‐chemical remanent magnetization (TCRM) within a breccia (or within in situ crust) would have depended upon the relative timing of oxide growth and dynamo cessation.…”
Section: Discussionmentioning
confidence: 98%
“…Gattacceca et al. () investigated the magnetic properties of NWA 7034, which revealed that the meteorite contains 15 wt% magnetite and maghemite, which makes it the most oxidized Martian meteorite so far studied. Furthermore, these authors speculate that low‐temperature hydrothermal alteration of NWA 7034 on Mars, possibly impact‐induced, produced some of the magnetite and altered magnetite to maghemite.…”
Section: Introductionmentioning
confidence: 99%